Synthetic and Structural Studies on Some New Butenolactones - Chamoli, R.P.; Prakhash, Shailendra; Kothiyal, D.P. (Asian Journal of Chemistry, 2010)
A series of new butenolactones has been synthesised by condensing a γ-oxoacid, β-( 4-phenylbenzoyl) acrylic acid with various mono-, di- and trihydroxyphenols.